Родовід одеського скульптора Бориса Едуардса - Кудлач, В. (Краєзнавство, 2017)
У статті робиться спроба з'ясувати родовід Бориса Едуардса, а також викласти окремі факти
біографії митця на основі його особової справи та спогадів скульптора і його щоденника, які він писав
на Мальті у 1920-1923 роках. The article is devoted to Boris Edwards, a prominent Odesa sculptor of European level, during its active
exhibition activities as a member of the Association of the South Russian artists in early 1890. Boris Edwards’
residence in Odesa during that period is studied on the base of reference books, exhibition catalogs of the association,
maps and some art history books.
Boris Edwards (1860-1924) – son of merchant, Russified British partial of Irish origin and Ukrainian aristocrat
of Maksimovic family. The article used documents from the collections of the Odesa National Research
Library, the State Archives of Odesa region, publications in scientific collections.
Edwards entered the history of Ukrainian art as a talented sculptor who has successfully worked as a muralist
and author of chamber works. Portrait genre and works of religious themes were the priority in his work.
Among the famous works of master - a group of sculptures «Christ and the Sinner» (silver medal at the World
Exhibition in Paris, 1900); busts of Louis Pasteur, «Shurka», monuments of Andreyevskiy E., A. Pushkin, M.
Gogol, Alexander Suvorov. Among his latest sculptures – «The lady in the chair» created in Malta, where the
sculptor emigrated in 1919. This work was exhibited in 1923 at the Colonial Exhibition.
In 1890, the enterprising sculptor opened the Atelier of Art and Industry sculpture at Sofievska Street, 18,
and four years later - a bronze foundry in the courtyard of his house in Sofievska Lane, which was the first
workshop of such type in Ukraine. В статье предпринята попытка выяснить родословную Бориса Эдуардса, а также изложить
отдельные факты биографии художника на основе его личного дела, воспоминаний скульптора и его
дневника, который он писал на Мальте в 1920-1923 годах.